2008 Oral Care Cost of Chiang Mai Community Hospitals - Lapying, Phenkhae; Keeddee, Jiraporn; Detpithak, Amporn (Journal of Health Science of Thailand, 2018)
The purpose of this study was to analyze full oral care cost of 3 community hospitals in Chiang Mai by conventional method. Shared cost was allocated as indirect cost by simultaneous equation method. The data was prospectively collected during April-June 2008. After 5 years full implementation of the Universal Health Coverage System, the average unit cost was 427.9 baht per visit or 687.8 baht per recipient which the operating and indirect costs were 516.8 and 171.0 baht, respectively. Per capita oral care cost of Civil Servant Medical Benefit Scheme, Social Security Scheme and Universal Health Coverage Scheme were assumed to be 104.6, 68.9 and 52.1 baht, respectively. The average per capita cost was 59.8 baht that increased 74.2 percent comparing to the budget year 2003.